A Contemporary Survey on Clustering Techniques for Wireless Sensor Networks - et. al., Kirubasri G, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Low power wirelessly interconnected devices forms a self-configured system called Wireless Sensor Network (WSN) which brings out numerous applications in today’s world. Nodes in WSN are spatially distributed and wirelessly inter-connected devices mainly involved in sensing the deployed region and recording the details of physical circumstances for instance hotness, humidity, noise vibrations, load etc,. The sensor observations are collected through a centralized node called sink from there the end-user control system receives the data for further analysis. After the deployment, nodes form a group among themselves called clusters and select one among them as Cluster Head (CH) which plays as a gateway to move the data further in the network. Clustering is very crucial in solving lots of issues in WSN especially in lifetime, scalability, energy saving and interoperability of the network. Many clustering approaches exist for WSN which are differs in terms of CH selection, cluster count, cluster structure, data aggregation policy, energy efficiency and Inter-cluster and Intra-cluster communication. This paper presents a robust comparative analysis of various clustering techniques with their merits and demerits in WSN. It also furnishes the CH selection and working principle of clustering protocols under each category which would help end user to choose the appropriate method with respect to the application requirements and also assist the researchers to address the revealed challenges in clustering process of WSN.